2014
DOI: 10.1182/blood-2014-05-578070
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of allelic ratio and insertion site in FLT3-ITD–positive AML with respect to allogeneic transplantation

Abstract: Key Points• In FLT3-ITD-positive AML, high allelic ratio and ITD insertion site in TKD1 predict for low complete remission rates and poor survival.• In FLT3-ITD-positive AML, allogeneic HSCT in first CR outweighs the negative impact of high allelic ratio on survival.The objective was to evaluate the prognostic and predictive impact of allelic ratio and insertion site (IS) of internal tandem duplications (ITDs), as well as concurrent gene mutations, with regard to postremission therapy in 323 patients with FLT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
306
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(327 citation statements)
references
References 48 publications
15
306
2
4
Order By: Relevance
“…In spite of these encouraging outcomes, several issues have not been addressed in the current study: the effect of FLT3 allelic ratio on transplant outcomes of elderly patients with FLT3-ITD-mutated AML, since evidence indicates that it can influence post-transplant outcomes in younger patients, 13 outcomes of patients with FLT3-TKD mutations, which were not included in this study, and the use of haploidentical donor transplants, as more patients are transplanted with a haploidentical donor when a HLA-matched donor is not available.…”
Section: Blood and Marrow Transplant Research (Cibmtr)mentioning
confidence: 94%
See 1 more Smart Citation
“…In spite of these encouraging outcomes, several issues have not been addressed in the current study: the effect of FLT3 allelic ratio on transplant outcomes of elderly patients with FLT3-ITD-mutated AML, since evidence indicates that it can influence post-transplant outcomes in younger patients, 13 outcomes of patients with FLT3-TKD mutations, which were not included in this study, and the use of haploidentical donor transplants, as more patients are transplanted with a haploidentical donor when a HLA-matched donor is not available.…”
Section: Blood and Marrow Transplant Research (Cibmtr)mentioning
confidence: 94%
“…9 On the contrary, several more recent studies indicate that AHCT is likely the best consolidation therapy for patients with FLT3-ITD-mutated AML, and should be performed as soon as possible in CR1. [10][11][12][13] In a study by DeZern and colleagues, there was significantly better RFS of FLT3-ITDmutated AML patients treated with AHCT as compared to the non-transplant group (54 months vs. 8.6 months), 12 while a study from the MD Anderson Cancer Center, which compared post-remission treatment with consolidation chemotherapy and AHCT in 227 FLT3-mutated AML patients who achieved CR1 after induction chemotherapy, showed that AHCT reduced the risk of relapse and improved both RFS and OS regardless of NPM1 status and FLT3 allelic ratio. 10 Moreover, our group analyzed the outcomes of 200 FLT3-mutated AML patients (either ITD or TKD mutations) treated with AHCT with various donor types, including haploidentical donor transplants.…”
mentioning
confidence: 99%
“…Of the 13 studies, one was deemed to have a low risk of bias, 342 10 were deemed to have a low to moderate risk of bias, § § § § and 2 were deemed to have a moderate risk of bias. 14,294 None of these studies were found to have methodological flaws that would raise concerns about the studies' findings.…”
mentioning
confidence: 99%
“…Moreover, our results are similar to published outcomes following transplantation for FLT3-ITD + AML using HLA-matched sibling, HLA-haploidentical, or HLA-matched unrelated donors and superior to the 20%-30% survival that has been reported with chemotherapy consolidation alone . 3,4,18,19 Therefore, UCB transplantation seems to overcome the adverse effects of FLT3-ITD + on AML. This is consistent with standard/conventional donor (sibling or unrelated donor) alloHCT studies that have demonstrated not only lower rates of disease relapse, 18 but also improved OS for FLT3-ITD + AML who undergo alloHCT, particularly patients with a higher FLT3-ITD to wild-type FLT3 allelic ratio.…”
mentioning
confidence: 99%
“…This is consistent with standard/conventional donor (sibling or unrelated donor) alloHCT studies that have demonstrated not only lower rates of disease relapse, 18 but also improved OS for FLT3-ITD + AML who undergo alloHCT, particularly patients with a higher FLT3-ITD to wild-type FLT3 allelic ratio. 3,4,19 The patient population and transplantation characteristics were homogenous, data were detailed [e.g. tyrosine kinase inhibitor (TKI) use] FLT3-ITD and the size of the study was reasonable (given frequency of FLT-ITD3 mutations and UCB transplantation) for a single center study.…”
mentioning
confidence: 99%